2012
DOI: 10.4314/ijbcs.v6i3.37
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and biological investigations of <em>Syzygium aromaticum</em> L. essential oil from Benin

Abstract: The essential oil obtained by hydrodistillation from seeds of Syzygium aromaticum (Myrtaceae) growing in Benin was analyzed by gas chromatography (GC) and gas chromatography-mass spectrometry (GC/MS). Twenty-one components, which represented 99.4% of the total constituents of the oil were identified. The essential oil is rich in hydrocarbons monoterpenic. The major constituents found were eugenol (60.4%), trans-β-caryophyllene (24.0%). The oil extract revealed an important antiradical activity and a high antim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
4
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
4
4
1
2
Order By: Relevance
“…This result is in agreement with those of Guan et al [21] and Nana et al [22] who obtained 11.5% and 10.54%, respectively. Although, these results are different from those acquired by several study [23][24][25][26][27] with a yield varying from 0.18 to 7.6%.…”
Section: Yield and Chemical Compositioncontrasting
confidence: 99%
See 3 more Smart Citations
“…This result is in agreement with those of Guan et al [21] and Nana et al [22] who obtained 11.5% and 10.54%, respectively. Although, these results are different from those acquired by several study [23][24][25][26][27] with a yield varying from 0.18 to 7.6%.…”
Section: Yield and Chemical Compositioncontrasting
confidence: 99%
“…In the present study the S. aromaticum essential oil exhibited a MBC varied from 5.45 to 10.9 mg/mL. A lower MBC was mentioned by Alitonou et al [24] with 3.12 mg/mL against E. coli ATCC 25922. Nazzaro et al [41] reported that "eugenol acts on bacteria by altering the cell membrane, affecting the transport of ions and ATP, and by changing the fatty acid profile of different bacteria".…”
Section: Antimicrobial Activitiessupporting
confidence: 45%
See 2 more Smart Citations
“…The traditional use of clove is supported by its many properties which have been described in numerous scientific reports highlighting its antioxidant, hypotensive, dental analgesic 3 , antibacterial 4 , antiinflammatory 5 and antifungal 6 activity, apart from the synergistic antimicrobial activity of the essential oil with other plants 7 which allows it to be considered with great potential for dental application 8,9 . The oral cavity is considered as an ecosystem.…”
Section: Introductionmentioning
confidence: 99%